Integrative attitudes of Ukrainian war refugees in two neighboring European countries (Poland and Hungary) in connection with posttraumatic stress symptoms and social support - Kovács, Judit; Csukonyi, Csilla; Kovács, Karolina Eszter; Liszka, Damian; Walawender, Paweł (Frontiers in Public Health, 2023)
Since February 24th, 2022, millions of Ukrainians have sought refuge in other, mainly European countries. Hungary, after Poland, is the second largest host of Ukrainian refugees. Only a portion of them are asylum seekers ( 11.0% in Poland and 1.1% in Hungary). The aim of the study is to compare the integrative acculturation attitudes between the war refugees residing in the two European countries. The comparison takes into account both the suffering of posttraumatic stress symptoms and social support. It is the first comparative study of this kind pertaining to the Ukrainian refugees in European countries. The data were obtained by a survey method using the modified CAPI (Computer Assisted Personal Interview) technique. The data analyzed were collected between November 21st and December 20th, 2022 from 728 adult Ukrainian individuals who crossed the borders of Poland and Hungary after February 24th, 2022. The research results show that refugees in Poland perceive significantly more social support and show stronger integrative attitudes than refugees in Hungary. The two samples do not differ regarding the presence of posttraumatic stress. The integrative attitudes proved not to be linked to gender and age, but linked to the host country. Besides social support and the host country, posttraumatic stress also proved to be a significant predictor of integrative attitudes.